2020
DOI: 10.1521/pdps.2020.48.3.234
|View full text |Cite
|
Sign up to set email alerts
|

The Psychodynamic Psychiatrist and Psychiatric Care in the Era of COVID-19

Abstract: Near the beginning of the COVID-19 pandemic, on April 13, 2020, about 50 members of the American Academy of Psychodynamic Psychiatry and Psychoanalysis convened through Zoom to talk about the impact of the pandemic on their practices, their patients, and themselves.* They offer their reflections through oral and written comments. Participants were encouraged to organize their contributions around the dimensions of administrative psychiatry, the structure of clinical care, the content of clinical care, the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Additionally, Jin et al (7) found that the need to belong can influence how one copes with public health emergency, thus reducing panic buying. Working through interpersonal dynamics and systems with the individual allows for improvement in communication styles, correction of cognitive distortions relating to previous interactions, and an increase in traits including patience, empathy and tolerance (6). Further, the role of past experiences is associated with the patient's present behavior and defense mechanisms (6).…”
Section: Psychological Causes Of Panic Buyingmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, Jin et al (7) found that the need to belong can influence how one copes with public health emergency, thus reducing panic buying. Working through interpersonal dynamics and systems with the individual allows for improvement in communication styles, correction of cognitive distortions relating to previous interactions, and an increase in traits including patience, empathy and tolerance (6). Further, the role of past experiences is associated with the patient's present behavior and defense mechanisms (6).…”
Section: Psychological Causes Of Panic Buyingmentioning
confidence: 99%
“…Working through interpersonal dynamics and systems with the individual allows for improvement in communication styles, correction of cognitive distortions relating to previous interactions, and an increase in traits including patience, empathy and tolerance (6). Further, the role of past experiences is associated with the patient's present behavior and defense mechanisms (6). Thus, if the individual is utilizing panic buying as a defense mechanism in order to create more adaptive coping mechanisms it is crucial for the clinician and the individual to process how the past is impacting the present.…”
Section: Psychological Causes Of Panic Buyingmentioning
confidence: 99%
See 3 more Smart Citations